Kajian Proses Penilaian Kewajaran atas Transaksi Sewa Pihak Berelasi - Irawan, Ferry; Safitri, Wirdatul Khusna Febri (Owner : Riset dan Jurnal Akuntansi, 2021)
This research aims to identify the fairness assessment procedures of related-party transactions by the tax assessor functional at KPP Madya Surabaya as well as the resistancesoccured whilemaking the assessment. This research applies qualitative method with descriptive research type. The focus of this research is to ascertain the assessment procedures carried out by the tax assessor functional at KPP Madya Surabaya with the types of transactions in the form of machine and equipment rental for the cigarette industry between the related-party (PT ABC and PT XYZ) The assessment is achived by adopting the income approach. The results of this study indicate that the valuation of fair market rental rates is implemented by referring to the investment feasibility criteria. The rental price is said to be reasonable if it yields NPV> 0, IRR>WACC and does not exceed the tenant's maximum return level (interest rate for investment credit in 2017 is 10.29% + bank credit risk (insurance 5%)).There are no specific provisions regarding how much numbers are used as long as they meet the criteria used by the tax assessor functional of the Surabaya Tax Office. The Resistance during the assessment process arises due to the lack of taxpayers and related parties disclosure regarding to the data and required information in the assessment. Apart from that, the assessment object which is classified as special property and the conditions during the field visit were different from the day of the assessment